Evaluation of the Next Birth After Caesarean (NBAC) clinic. - Martin, Tracy Lee (Curtin University, 2012)
Developing, implementing and evaluating models of care that reduce the caesarean section (CS) rate have been a health care priority in Australia since the 1990’s. There is minimal evidence examining models of care that aim to nurture women’s emotional well-being after CS; as well as providing consistent evidence-based information and promoting safe and successful vaginal birth in the subsequent pregnancy. Furthermore the experiences of midwives working in these models have been overlooked.